2019
DOI: 10.33966/hepj.2.1.12918
|View full text |Cite
|
Sign up to set email alerts
|

Education pathways, mentoring and future intentions of nurse and midwifery consultants in a NSW Health District

Abstract: Clinical Nurse and Midwifery Consultants (CNC/CMCs) play an important role within NSW Health Services. They are required to function within five domains of practice: clinical service and consultancy, clinical leadership, research, education, and clinical services planning and management. This study engaged with one Health District's current CNC/CMC network members with a view to informing the development of a strategy for career and succession planning. One hundred CNC/CMCs were invited to participate in an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Another study showed that midwives require an additional 30 minutes for an effective depression screening 23 . These findings are consistent with research by Edga (2010), which reported that midwives need more time to conduct physical examinations, leaving most women with psychological stress untreated 24 . Another challenge identified is the healthcare professionals' lack of knowledge about managing depression and the absence of specific Standard Operating Procedures (SOP) or guidelines for managing depression in pregnant women at community health centers.…”
Section: Factors Potentially Hindering the Management Of Depression I...supporting
confidence: 91%
“…Another study showed that midwives require an additional 30 minutes for an effective depression screening 23 . These findings are consistent with research by Edga (2010), which reported that midwives need more time to conduct physical examinations, leaving most women with psychological stress untreated 24 . Another challenge identified is the healthcare professionals' lack of knowledge about managing depression and the absence of specific Standard Operating Procedures (SOP) or guidelines for managing depression in pregnant women at community health centers.…”
Section: Factors Potentially Hindering the Management Of Depression I...supporting
confidence: 91%